1980
DOI: 10.1111/j.1365-2125.1980.tb04919.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic effects of guanfacine.

Abstract: 1 The haemodynamic mechanism of action of guanfacine 4 mg intravenously was investigated in resting conditions and during exercise for up to 20 h after administration of the drug. Cardiac output and pulmonary arterial pressure were determined by the Swan-Ganz thermodilution method. Blood pressure was measured directly. 2 During and immediately after intravenous administration of guanfacine, blood pressure peripheral resistance and pulmonary arterial pressure increased (in keeping with an xsympathomimetic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Its long elimination half-life, shown to be over 17 h in pharmacokinetic studies in animals, nonmotensive volunteers and hypertensive patients (Kiechel, 1980;Kirch, 1980) and its long duration of action make guanfacine suitable for twice daily or even once daily dosing, as confirmed by the results of short-term clinical trials (Reid & Zamboulis, 1980;Magometschnigg, Hitzenberger & Bonelli, 1980). This multicentre study was designed to establish the usefulness of guanfacine for long-term treatment of all forms and stages of hypertension in routine practice, with special regard to the following questions:…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Its long elimination half-life, shown to be over 17 h in pharmacokinetic studies in animals, nonmotensive volunteers and hypertensive patients (Kiechel, 1980;Kirch, 1980) and its long duration of action make guanfacine suitable for twice daily or even once daily dosing, as confirmed by the results of short-term clinical trials (Reid & Zamboulis, 1980;Magometschnigg, Hitzenberger & Bonelli, 1980). This multicentre study was designed to establish the usefulness of guanfacine for long-term treatment of all forms and stages of hypertension in routine practice, with special regard to the following questions:…”
Section: Introductionmentioning
confidence: 78%
“…hospitalized and ambulatory hypertensives has been recorded in a large number of controlled clinical trials THE antihypertensive efficacy of guanfacine (Estulic , (Jiattela, 1976a;1976b;Dubach, Huwyler, Sandoz clinical code BS 100-141, Lon 0798) in Radielovic & Singeisen, 1977;Esch, 1976 Sabel & Heidland, 1978;Kirch & Distler, 1978;Seedat, 1978;Lochaya, Thongmitr & Suvachittannont 1979). Its long elimination half-life, shown to be over 17 h in pharmacokinetic studies in animals, nonmotensive volunteers and hypertensive patients (Kiechel, 1980;Kirch, 1980) and its long duration of action make guanfacine suitable for twice daily or even once daily dosing, as confirmed by the results of short-term clinical trials (Reid & Zamboulis, 1980;Magometschnigg, Hitzenberger & Bonelli, 1980). This multicentre study was designed to establish the usefulness of guanfacine for long-term treatment of all forms and stages of hypertension in routine practice, with special regard to the following questions:…”
Section: Introductionmentioning
confidence: 96%
“…Steady‐state blood levels are achieved within 4 days in most patients. In contrast to clonidine, studies in hypertensive patients have suggested that guanfacine reduces BP mainly by reducing total vascular resistance rather than cardiac output 19,20 . Guanfacine reduces resting heart rate with minimal effect on heart rate during exercise 19 .…”
Section: Guanfacinementioning
confidence: 99%
“…In contrast to clonidine, studies in hypertensive patients have suggested that guanfacine reduces BP mainly by reducing total vascular resistance rather than cardiac output 19,20 . Guanfacine reduces resting heart rate with minimal effect on heart rate during exercise 19 . In contrast, guanfacine reduces TPR similarly both at rest and during exercise with minimal effects on cardiac output 19 .…”
Section: Guanfacinementioning
confidence: 99%
“…The fall in BP due to guanfacine is accom panied by a decrease in peripheral resistance [Ehringer et al, 1980;Magometschnigg et al, 1980]. Indometacin has been showrn to in crease the peripheral resistance in normal volunteers [Wcnmalm.…”
Section: Discussionmentioning
confidence: 99%